The ability of CSST to determine the orbital solutions of SB1s - Wang, Xiaoli; Xia, Fang; Fu, Yanning; Chen, Yue (Frontiers in Astronomy and Space Sciences, 2023)
The single-lined spectroscopic binaries (SB1s) are composed of two components with large difference in masses and in physical properties. The orbital and physical parameters of a large number of such binary systems are unknown due to lack of necessary observations. Compared with SB2s, SB1s can provide much more stringent constraint to stellar evolutionary models at a single age. Besides, the fainter components of SB1s are likely to be compact celestial objects, such as a black hole or a neutron star, it is therefore interesting to determine their masses and physical properties. CSST provides an excellent opportunity to study SB1s especially nearby ones, since it can detect astrometric wobble at milliarcsecond level. This implies that if the motion of the visible components can be detected, the full motion of the SB1s can be determined. In this paper, we aim to analyse the ability of CSST to improve the orbital solutions of nearby SB1s based on the available data by adding simulated CSST data of different observation times. The orbital solutions of binaries determined from non-single-star orbital models for sources compatible with combined astrometric + single lined spectroscopic orbital model of Gaia DR3 are served as the research sample to reproduce the orbital elements by fitting simulated CSST data.